IMPROVEMENT OF LOGISTICS SYSTEM OF MUNICIPAL TRANSPORT MANAGEMENT - Boiko, Volodymyr (Вісник Черкаського державного технологічного університету, 2020)
It is established that the use of the transport logistics theory in passenger transportation makes it possible to eliminate complex contradictions that arise, on the one hand, between passenger and transport enterprises, and on the other – between transport enterprises and society. It is theoretically proved that the use of logistical approaches in the organization of municipal passenger transportation gives a transport company advantages in the fight for the market and passengers, leads to lower costs and cost of services, improves the quality of service. On the basis of the analysis of logistical approaches in municipal transport management, the improvement of logistics transport system is carried out, which, unlike the existing ones, characterizes branched multithreaded urban transport processes and systems and is built on the basis of modern information and computer technologies.